2013
DOI: 10.1002/jee.20024
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Information Literacy Skills Demonstrated in an Engineering Design Task

Abstract: Background Practicing engineers must continuously renew their knowledge and skills in order to remain competitive in the field. Yet, recent studies have found very little improvement in engineering graduates' lifelong learning skills. Research on information literacy, a critical component of lifelong learning, in technical fields is limited. Purpose/Hypothesis This study sought to evaluate the information skills of first‐year engineering students. Specifically, it investigated the extent to which students gath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 36 publications
4
66
0
Order By: Relevance
“…A common error was to reference their information sources without providing fields necessary to trace the original sources. These kind of difficulties were also found by Wertz, Purzer, Fosmire & Cardella (2013) among engineering freshmen students. It can be concluded that educational intervention allowed the students to recognize the importance of using bibliographic references; however, it is necessary to reinforce teaching related to the citation and referencing format at any phase of the intervention.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…A common error was to reference their information sources without providing fields necessary to trace the original sources. These kind of difficulties were also found by Wertz, Purzer, Fosmire & Cardella (2013) among engineering freshmen students. It can be concluded that educational intervention allowed the students to recognize the importance of using bibliographic references; however, it is necessary to reinforce teaching related to the citation and referencing format at any phase of the intervention.…”
Section: Discussionmentioning
confidence: 57%
“…In other cases, the students cite the sources correctly, but without any reference to them in the text. These results indicate that the documentation skills of engineering students are an area that requires further research (Wertz, Purzer, Fosmire, & Cardella, 2013).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations